Problems of Atomic Science and Technology 2020
DOI: 10.46813/2020-130-185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corona Discharge on Aspergillus Niger Spores And Cyathus Olla Mycelium Growth

Abstract: The article presents an investigation of the influence of the corona discharge with needle-ring electrode configuration on the efficiency of Aspergillus niger spore germination and Cyathus olla mycelium development. Current-voltage characteristics were measured for different distances between the needle and the metal ring. The plot of the dependence of conductance on voltage was built and the corona discharge breakthrough voltage was determined to be (2.7±0.1) kV. The treatment of Aspergillus niger spores was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The observed correlation between ozone generation and bactericidal effect confirmed the importance of ROS in chemically generated stress, resulting in the inactivation of microorganisms. Recently, Nedybaliuk et al [299] investigated the influence of corona discharge (needle-ring geometry) on the efficiency of Aspergillus niger spore germination and Cyathus olla mycelium development. The Aspergillus niger spores were treated at different developmental stages (i.e.…”
Section: Corona Dischargementioning
confidence: 99%
“…The observed correlation between ozone generation and bactericidal effect confirmed the importance of ROS in chemically generated stress, resulting in the inactivation of microorganisms. Recently, Nedybaliuk et al [299] investigated the influence of corona discharge (needle-ring geometry) on the efficiency of Aspergillus niger spore germination and Cyathus olla mycelium development. The Aspergillus niger spores were treated at different developmental stages (i.e.…”
Section: Corona Dischargementioning
confidence: 99%
“…One method to prevent fungi's negative impact on plant growth and storage is plasma treatment [4]. Nonequilibrium atmospheric pressure plasma has many applications in various fields, such as surface treatment, combustion enhancement, bacterial inactivation [4][5][6], and contamination reduction [7]. Plasma is an effective sterilization method and can be used for seed disinfection as an alternative to chemicals [8].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we studied the influence of the corona discharge on the germination of spores and the development of higher fungi mycelium [6]. Depending on the treatment mode, the corona discharge was able to either speed up or slow down the growth of the higher fungi mycelium [6]. Works [7,8] have also shown that plasma influences the surface tension of liquids.…”
Section: Introductionmentioning
confidence: 99%